Pengaruh E-Promotion, Voucher Diskon Dan E-Review Restoran Terhadap Keputusan Pembelian Di Platform Shopeefood (Studi Kasus Mahasiswa Universitas Islam Malang) - Ferdiansyah, Septian; Basalamah, Muhammad Ridwan; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine the influence of E-Promotion, Voucher Discounts, and E-Reviews on Purchase Decisions on the ShopeeFood platform. The research was conducted as a case study involving 111 students from the Islamic University of Malang as respondents, selected through purposive sampling technique. The data were analyzed assistance of SPSS version 26. The results indicate that E-Promotion, Voucher Discounts, and E-Reviews have a significant effect on Purchase Decisions, both simultaneously and partially. These findings demonstrate that digital promotions, discount offers, and online customer reviews play a significant role in influencing consumer purchasing behavior on online food delivery platforms such as ShopeeFood. Keywords: E-Promotion, Voucher Discounts, E-Reviews, Purchase Decision, ShopeeFood